UNDERSTANDING THE ASYMMETRIC EFFECTS OF EXCHANGE RATE ON ECONOMIC GROWTH: EVIDENCE FROM INDIA - Shaikh, Zakir Hossen; Husain, Shah; Alam, Mohammad Noor; Baig, Imran Ali; Rana, Minakshi (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This study examines the short-term and long-term relationships between economic growth, exchange rate fluctuations, money supply, and government expenditure in India from 1980 to 2022. The study employs econometric techniques such as unit root tests, Nonlinear autoregressive distributed lag (NARDL) model, FMOLS & DOLS tests, and the Granger causality test is used to determine the direction of causal relationships. The data utilized in this study were collected from the Handbook of India’s Statistics (RBI) and World Development Indicators (WDI). The unit root tests indicate mixed order of integration for the selected variables. The results of the NARDL model confirm a long-term relationship among economic growth, exchange rate changes, money supply, and government expenditure. The findings indicate that undervaluation negatively affects economic growth in India, whereas overvaluation promotes it. Furthermore, the analysis reveals an asymmetric impact of exchange rate changes on economic growth. The Wald test further supports the presence of asymmetry in both the short-run and long-run. The causality test results show bidirectional causality between exchange rates, government expenditure, and economic growth, while unidirectional causality runs from money supply to economic growth. Based on the empirical findings, some policy implications may be suggested to the government. The exchange rate-controlling organization should emphasize restoring stability and pursue the establishment of a stronger exchange rate to achieve the goal of sustained economic growth and, ultimately, sustainable development